American Foreign Policy of the Twenty-first Century: Security through the Promotion of Democracy - Thompson, Grace (Maine Policy Review, 2005)
Each year, the Margaret Chase Smith Library sponsors an essay contest for Maine high school seniors. We feature here Grace Thompson’s 2005 first place prize-winning essay, which draws upon historical examples as well as personal experiences and opinions to discuss American foreign policy for the 21st century.